Berinovasi dengan TikTok: UMKM Lokal dan Langkah-Langkah Menghadapi Dinamika E-Commerce di Tahun 2024 - Siswanto Siswanto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
In the growing digital era, the use of TikTok by local Micro, Small, and Medium Enterprises has become a significant concern in an effort to expand markets and increase sales. This article analyzes the challenges and strategies that can be adopted by in facing e-commerce dynamics and utilizing the TikTok Platform as E-Commerce effectively. The research method used is using a qualitative approach method by conducting literature studies and literature studies. The method for data collection is obtained from the official website (e-commerce usage data) and studying theories from various literatures related to the research. The results show the importance of efficient advertising budget management, optimization of logistics and delivery, improved skills in content creation, strategic collaboration, and campaign performance monitoring as key steps in facing challenges and taking advantage of opportunities in TikTok Commerce. Through a deep understanding of market dynamics and the implementation of appropriate strategies, MSMEs can strengthen their presence in TikTok Commerce and increase their competitiveness in the competitive e-commerce ecosystem. Translated with DeepL.com (free version)